The Effect of Nutrition Education and Iron Supplementation (Iron Tablets) on Knowledge and Hemoglobin Levels in Adolescent Girls - Riezky Faisal Nugroho; Erika Martining Wardani; Nuning Marina Pengge; Nurul Hindaryani (Pontianak Nutrition Journal (PNJ), 2026)
Anemia is a common health problem among adolescents, especially girls, due to increased iron requirements during puberty. Inadequate iron intake can lead to decreased hemoglobin levels and a higher risk of anemia during pregnancy. This study aimed to determine the effect of nutrition education and iron tablet supplementation (Tablet Tambah Darah/TTD) on knowledge and hemoglobin levels among adolescent girls at MTsN 3 Surabaya. This study used a quasi-experimental design with a nonrandomized pretest–posttest control group. A total of 80 respondents were selected using proportional stratified random sampling. Data were analyzed using the Kruskal-Wallis and Wilcoxon tests. The findings showed a significant effect of nutrition education on knowledge improvement (p = 0.002) and a significant effect of iron tablet supplementation on hemoglobin levels (p = 0.001). Nutrition education and iron tablet supplementation significantly improved knowledge and hemoglobin levels among adolescent girls. Schools and health centers are encouraged to provide regular counseling and monitoring of iron tablet consumption to prevent anemia.